School's Cool Lickety Split - Williams, Harland (Durkin Hayes Publishing Ltd., 1993)
Lickety Split worries about going to school but when he gets there he really likes it.
Keywords: Dinosaurs & Prehistoric Creatures; Schools; Self-acceptance; Stories In Rhyme; Dinosaurs; Nature